The Internet Marketing of Emerging Local Muslim Tourist Destination in Banyuwangi, Indonesia - Nur E Suriani, Dian Y Reindrawati, Sulikah Asmorowati, (Opción)
This paper aims to analyze the use of internet marketing in emerging local Muslim tourist destination in Banyuwangi, Indonesia, named Santen Beach. Since 2017, Santen Beach has been branded by the local government as Sharia Beach; the beach that complies with Islamic Sharia values. This sharia branding of the beach has brought an interesting idea of looking at how the management of the beach utilizes internet in order to promote the beach and supports its branding. This research employs qualitative approach, by interviewing beach’s officers and visitors. The results show that the use of internet marketing in Santen Sharia Beach has not been optimal.